TINJAUAN YURIDIS TERHADAP PEMBUATAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) OLEH NOTARIS DENGAN MENCANTUMKAN KOP NOTARIS - , DWI AULIA DESTIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research about the issuance of Power of Attorney to Impose Mortgage (PAIM) by notary by listing the letterhead of notary represented a research about the validity and authenticity of notarized PAIM. Whereas found several notaries issuing PAIM with following to the provision of Perkaban Number 8 of 2012, which about the obligation to put the listing of the letterhead in the beginning of the notarized PAIM deed, whilst in the article 38 of Law Number 2 of 2014 regarding the provision of issuance of notarial deed, there was no provision about listing the letterhead within the beginning of the deed. Therefore, an analysis of the effectiveness of notarized PAIM in the registration to the Land official, as well as to find out the legal power of notarized PAIM with listing the letterhead within the beginning of the deed. This research was an empirical legal research, using primary data and proceeded in prior with secondary data. The obtained data in this research had been analyzed qualitatively, and the result was elaborated descriptively. A registered notarized PAIM before the Yogyakarta Land Official shall follow the provision of Perkaban Number 8 of 2012, by listing the letterhead, without listing the letterhead